Numerical Simulation as a Tool to Predict Sheet Metal Forming Process of TRIP Steel HCT690 - Korecek, David; Solfronk, Pavel; Sobotka, Jiri (Manufacturing Technology Journal, 2020)
The submitted paper describes the utilization of numerical simulations to predict sheet metal forming process of ultra-high strength TRIP steel HCT690T EN 10346. Numerical simulations of production processes are increasingly becoming an integral part of the pre-production stage of the sheet metal forming processes. Furthermore, it is possible to use these numerical simulations not only in the production itself (e.g. to test the validity of the process or influence of process parameters, etc.), but also in the post-production stage as a tool for various controls and comparative measurements with the real processes, testing the capacity of the process and so on. For proper and the reliable course of the numerical simulation must be at first obtained and then entered the correct input data into the numerical simulation software. This data enters into the simulation in the form of definition the material computational model. Such computational model is defined by using material data and individual material characteristics at different loading methods. With regard to the material model and the given process parameters, it is possible to realize the process simulation, which takes place in the numerical simulation software - in this paper was used PAM STAMP 2G from the French company ESI Group.
Keywords: Numerical Simulation; Sheet Metal Forming; Spring-back; Material Computation Model; Ultra-high Strength Steel